(In)visibilidade das mulheres na pesca artesanal: uma análise sobre as questões de gênero na colônia de pescadores e pescadoras z-16 em Miracema do Tocantins/TO - Mendes, Soraya Helena de Araújo (Universidade Federal do Tocantins, 2016)
This research aimed to analyze (in)visibility of fishing activities carried out by fishers associated with Cologne Fishermen Craft Professionals Z-16 Miracema do Tocantins in Tocantínia – COPEMITO. The term (in)visibility was one definition used by the research author in question, because of evidence that the fishing activities that women do are (invisible both for them and for the others. In this sense, this study sought to give visibility, these activities, which are (in) visible due to gender, since these act as a marker cultural in the process of construction and social reproduction of subjects. We intend to identify and reflect on the kind of places and if these legitimize inequalities between men and women in the artisanal fishing universe. The methodology dopted in the study was qualitative nature the use of oral history. The data were interpreted based on gender perspective, understood in this study as the first way of constructing the social relations of power and subordination between men and women, whose foundation heory is based on studies undertaken by Scott (1990, 2012). Based on this, the, results of this research show the fishers of COPEMITO perform all, activities that constitute professional artisanal fishing, from the making of fishing tackle to the fish processing are therefore visible. However, there are diferences among women living with partner, of which are single, since the first, ince the first conceive their activities as "help" and the latter consider direct participants in activity, which legitimizes the existence of gender inequalities in the fisheries sector. The data allows also realize hat women need greater coordination along with the social organization of movements category. In this perspective, we infer that it is necessary for the consolidation of public policies that include the fishers and rovide access to this their social, social security and labor rights.